Positive Chaos dalam Kekacauan Informasi di Era Digital - Afina Fahru Miliana (SOSIAL : Jurnal Ilmiah Pendidikan IPS, 2024)
The advancement of information and communication technology has resulted in a lot of irregular, random and chaotic information outbursts. If the chaos of information in this digital era can be associated with chaos theory, then there will be a new perspective where chaos is not seen as something negative but something positive or positive chaos. By using a literature study, this study found the effect of positive chaos, namely an increase in digital literacy in society as a form of public awareness in receiving information. In addition, government and researcher efforts continue to be increased to develop digital literacy programs that must be in line with advances in information and communication technology.